2002
DOI: 10.1080/15391523.2002.10782351
|View full text |Cite
|
Sign up to set email alerts
|

Using Parent–Student Pairs for Internet Instruction

Abstract: Student and parent attitudes toward school-based Internet use were explored usingparent-student pairs. An inter generational approach positioned 54 pairs of young adolescents and their parents as co-learners for simultaneous Internet instruction, while another 51 parent-student pairs were given separate Internet instruction. This study; examined the effoct of instructional conditions using pre-and post-instruction attitude surveys and interviews. Survey analyses included descriptives, reliability measures, fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 8 publications
0
8
0
Order By: Relevance
“…They describe a case where a telecentre project had to provide separate locations for young people and adults to participate in activities, as each group was daunted by the presence of the other. However, researchers have found that there are benefits to be derived from inter-generational interaction associated with the use of technology, such as knowledge sharing and increased understanding in interactions across generations (Caskey, 2003;Kolodinsky et al, 2002;McKay, 2005;Wright, 2000). It has also been found that increased digital inclusion of the elderly can facilitate social inclusion (Ferlander and Timms, 2006).…”
Section: Generational Influencementioning
confidence: 94%
“…They describe a case where a telecentre project had to provide separate locations for young people and adults to participate in activities, as each group was daunted by the presence of the other. However, researchers have found that there are benefits to be derived from inter-generational interaction associated with the use of technology, such as knowledge sharing and increased understanding in interactions across generations (Caskey, 2003;Kolodinsky et al, 2002;McKay, 2005;Wright, 2000). It has also been found that increased digital inclusion of the elderly can facilitate social inclusion (Ferlander and Timms, 2006).…”
Section: Generational Influencementioning
confidence: 94%
“…Some studies have focused on peripheral issues such as the roles individuals can adopt in collaborative information seeking (Prekop, 2002), attitude changes in intergenerational collaboration (Caskey, 2003), and gender differences in group-based information seeking (Large, Beheshti & Rahman, 2002). Another line of research is directed towards designing interfaces and support tools to foster collaborative information-seeking activities (Chau, Zeng, Chen, Huang & Hendriawan, 2003;Druin et al , 2003;Twidale & Nichols, 1998).…”
Section: Introductionmentioning
confidence: 98%
“…Moreover, the findings suggest that just as parents with limited literacy skills can still inspire reading development in their children by sharing books with them, so too might parents with limited computer skills be able to augment Downloaded by [University of California, San Diego] at 08:22 27 March 2016 their children's skills simple by interacting with them on the computer (rather than teaching them in a more formal manner). Finally, programs such as Head Start and physicians' offices might develop programs like Reach Out and Read to model computer learning skills to young children for parents lacking in such skills, as similar programs were proven to be beneficial to both parents and children (Caskey, 2002).…”
Section: Discussionmentioning
confidence: 99%